(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
The Europe 2020 strategy emphasizes that social enterprises are very useful to the society as an important element of the social economy. As “hybrid” organizations, social enterprises seek to manage the potential tension between social and business aims. The purpose of this article is to disclose how social enterprises may harmonize social and for-profit purposes. The present research promotes sharing of best practices in the field of social business. The methods of the research are analysis of scientific literature and expert interview. The research revealed that investment into human resources of the company, strong focus on the mission hybridity and organization strategy, sufficient communication with the stakeholders, and relevant monitoring of the organization’s financial and statistical indicators can help social entrepreneurs to find a balance between social and profit ambitions. The research confirmed that the phenomenon of mission drift does not depend on how much the country is mature in terms of experience with hybrid organizations and social enterprises in particular. The study can help to better understand the nature of mission drift and to plan problem mitigating solutions. Keywords: Social enterprise, hybrid organizations, mission drift, Baltic States